Analisis Dan Perancangan Jaringan Komputer Sekolah Dasar Islam Sains Dan Teknologi Ibnu Qoyyim Surakarta - Yunus Irawan; Abdillah Baraja (APMMI - Asosiasi Profesi Multimedia Indonesia, 2012)
Abstact : The development of technology at this present and many people needs data processing and the organization or educations institution for their daily activities as well. It can not separated from the computer technology which can assist and provide data management and storage easy. In an organitation such as educational institutions at all times conduct activities related to processing and storage data, it is necessary a communication system where the data need to be processed, data storage and exchage of information between each other can be done quickly and efficiently. The Elementary School of Sains and Technology which is located in Gajah Mada Street , Banjarsari Surakarta region have not apply integrated computer network system. The data collection conducted be teacher from one computer to another computer has many obtacles. This is because computers are not able to make sharing data and as well as some importants data storage in each teacher’s notebook privately. The design is made, because of the difficulty of retrieval of data from one computer to another. With this design, we hope that the teacher can retrieve the data easier. The design aims is to make a planning of computer network system design. The research methodology used observation, literature, interviews, analysis, planning. The results of this design is expected to give reference and tools for the School of Science and Technology Surakarta to build the computer network system design easy to implement in near the future. Keyword : computer network , sharing data